Capacitance-transient spectroscopy on irradiation-induced defects in Ge - Nylandsted Larsen, Arne; Mesli, Abdelmadjid (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
Recent studies of room-temperature irradiation-induced defects in Ge using space-charge capacitance-transient spectroscopy are reviewed. From these measurements only two defect complexes have been unambiguously identified until now: the E-center (the group-V impurity-vacancy pair) and the A-center (the interstitial oxygen-vacancy pair). However, contrary to silicon where each of these centers introduces only one energy level, in germanium the E-center has three energy levels corresponding to four charge states (=, –, 0, +), and the A-center has two levels corresponding to three charge states (=, –, 0). Another feature specific to each material is the anneal temperature. Both centers disappear below 150°C in germanium, whereas in silicon the E-center anneals out at ~150°C, depending on the charge state, and the A-center is stable up to 350°C.
Optica Applicata, Vol. 36, 2006, nr 2-3, s. 245-256
Keywords: optyka; Ge-defect; deep level transient spectroscopy (DLTS); Laplace DLTS